Surgical outcomes of the endoscopic endonasal transsphenoidal approach for large and giant pituitary adenomas: institutional experience with special attention to approach-related complications - Constantino, Edson Rocha; Leal, Rafael; Ferreira, Christian Cândido; Acioly, Marcus André; Landeiro, José Alberto (Arquivos de Neuro-Psiquiatria, 2016)
Objective In this study, we investigate our institutional experience of patients who underwent endoscopic endonasal transsphenoidal approach for treatment of large and giant pituitary adenomas emphasizing the surgical results and approach-related complications.Method The authors reviewed 28 consecutive patients who underwent surgery between March, 2010 and March, 2014.Results The mean preoperative tumor diameter was 4.6 cm. Gross-total resection was achieved in 14.3%, near-total in 10.7%, subtotal in 39.3%, and partial in 35.7%. Nine patients experienced improvement in visual acuity, while one patient worsened. The most common complications were transient diabetes insipidus (53%), new pituitary deficit (35.7%), endonasal adhesions (21.4%), and cerebrospinal fluid leak (17.8%). Surgical mortality was 7.1%.Conclusions Endoscopic endonasal transsphenoidal surgery is a valuable treatment option for large or giant pituitary adenomas, which results in high rates of surgical decompression of cerebrovascular structures.
Keywords: endoscopic endonasal approach; giant pituitary adenomas; large pituitary adenomas; complication rates